Evaluation of the semen characteistics after induced spermiation in the bullfrog Lithobates catesbeianus - doi: 10.4025/actascibiolsci.v35i3.14780 (Acta Scientiarum. Biological Sciences, 2013)
Evaluation of semen characteristics after hormonal induction of the bullfrog could provide valuable information on the gametes of this species, which may be useful for projects related to artificial fertilization, animal improvement, and cryopreservation. Bullfrog males were induced to spermiate with buserelin acetate (GnRHa), and their semen was subsequently analyzed. GnRHa (0.4 Î¼g) was administered to the bullfrog males with secondary sexual characteristics such as weight > 200 g, yellow chin, nuptial callus, and amplexus reflex, being the semen collected after 60 min. The semen volume was 5.76 mL, light-colored. The other characteristics of the semen were: vigor of 4.80, motility of 93%, concentration of 14.24 Ã— 106 mL-1, and content of normal spermatozoa of 70%. The volume, color, vigor, motility, sperm concentration, and content of normal spermatozoa were adequate in these bullfrog semen samples. Evaluation of the bullfrog semen samples based on this set of parameters is essential for decision-making about the quality and destination of the semen.